Effect of Some Viticultural Parameters on the Grape Carotenoid Profile - Oliveira, Carla (2011)
The effect of some viticultural parameters on the grape carotenoid profile was investigated. Grape cultivar, ripeness stage, sunlight and shade exposure, altitude, and vegetative height were studied. Differences between cultivars were observed in eight different black grape varieties: Touriga Brasileira (TBR), Tinta Barroca (TB), Tinta Amarela (TA), Souza˜o (S), Touriga Franca (TF), Touriga Nacional (TN), Tinta Roriz (TR), and Tinto Ca˜o (TC), from the Douro region. TA and TBR clearly produced higher concentrations of carotenoids. Results showed that carotenoid content decreased during ripening. Decreases of lutein were observed until 66%, whereas â-carotene slowly decreased, having a constant level until the harvest date. Carotenoid contents were consistently higher in grapes exposed to shade than in those exposed to direct sunlight in both studied white grape varieties, Maria Gomes (MG) and Loureiro (L). In the Douro Valley, high-elevation terraces, which presented a lower temperature and higher humidity during the maturation period, appeared to produce grapes with higher carotenoid values. Grapes grown with higher vegetative height seem to have higher carotenoid levels; furthermore, grapes grown with lower vegetative height had higher weight and sugar concentrations.